2017
DOI: 10.1128/genomea.00850-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of a Salmonella enterica Serovar Typhi Strain Resistant to Fourth-Generation Cephalosporin and Fluoroquinolone Antibiotics

Abstract: Typhoid is endemic in developing countries. We report here the first draft genome sequence of a Salmonella enterica serovar Typhi clinical isolate from Pakistan exhibiting resistance to cefepime (a fourth-generation cephalosporin) and fluoroquinolone antibiotics, two of the last-generation therapies against this pathogen. The genome is ~4.8 Mb, with two putative plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…These events shifted the first-line and empirical treatments to other classes of antimicrobial agents, such as ceftriaxone (cro) and azithromycin. Alarmingly, reports of resistance against these agents have now been published ( 6 , 12 18 ). Moreover, a recent report from Pakistan described the first large-scale outbreak of an S .…”
Section: Introductionmentioning
confidence: 99%
“…These events shifted the first-line and empirical treatments to other classes of antimicrobial agents, such as ceftriaxone (cro) and azithromycin. Alarmingly, reports of resistance against these agents have now been published ( 6 , 12 18 ). Moreover, a recent report from Pakistan described the first large-scale outbreak of an S .…”
Section: Introductionmentioning
confidence: 99%
“…The Bangladesh and Iraq isolates also harbor bla CTX-M ESBL genes, but the Iraq isolate reportedly had an IncN plasmid, which differs from the IncY plasmid identified in this study. A draft genome of the Pakistan case from Rawalpindi has been released ( 20 ), and it harbors the same plasmid that we identified in the Sindh, Pakistan, cases.…”
Section: Discussionmentioning
confidence: 73%
“…Of those, only four individual cases (single patients) have reported S . Typhi that was also both MDR and fluoroquinolone resistant ( 16 20 ). These cases originated from Iraq, Bangladesh, India, and Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates from Iraq and Bangladesh were found to harbor blaCTX-M genes, and the Iraqi isolate was found to have an IncN plasmid whereas the isolates from Pakistan were having the blaCTX-M gene and the IncY plasmid [4]. A similar plasmid was identified from the draft genome of a single isolate from Rawalpindi, Pakistan as identified in the isolate from Sindh, Pakistan [4,22].…”
Section: Discussionmentioning
confidence: 83%
“…The literature has proposed the term "extensively drugresistant" (XDR) for the S. Typhi isolates which are resistant to five antimicrobial agents consistent with the nomenclature recommended for other pathogenic bacterial species [4,14]. The sporadic cases of cephalosporin-resistant have been reported in few studies and of which few individual cases have found XDR S. Typhi isolates which were resistant to cephalosporins and fluoroquinolone in addition to the MDR phenotypes [5,7,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%